Eva e il serpente. Primi appunti su bellezza e conoscenza - Yaryshkina, Polina (Scenari, 2024)
The aim of this article is to provide additional and new arguments to the idea of the centrality of the sensible element, according to one of the basic tenets of Western aesthetic theory, within cognitive praxis. To do so, this research uses a figure present, as Jung would have said, within the archetypes of the collective iconographic imagination: the snake. In particular, the choice was made to circumscribe the reswwearch within the Judeo-Christian cultural horizon (beginning with its sacred scriptures), identifying parallels with the Christian and pre-Christian traditions of Slavic culture, with attention also paid to etymological analyses of European and Slavic languages. Thus, a juxtaposition emerges between the figure of the serpent and the feminine, a juxtaposition that, starting from the biblical text, becomes a harbinger of developments that can be followed and deepened within disciplines such as psychoanalysis and archaeological research.